Oral Transmission of Chagas Disease by Consumption of Açaí Palm Fruit, Brazil - Aglaêr A. Nóbrega; Marcio H. Garcia; Erica Tatto; Marcos T. Obara; Elenild Costa; Jeremy Sobel; Wildo N. Araujo (Emerging Infectious Diseases, 2009)
In 2006, a total of 178 cases of acute Chagas disease were reported from the Amazonian state of Pará, Brazil. Eleven occurred in Barcarena and were confirmed by visualization of parasites on blood smears. Using cohort and case–control studies, we implicated oral transmission by consumption of açaí palm fruit.